An artificial intelligence-based model for prediction of clonal hematopoiesis variants in cell-free DNA samples - Gustavo Arango-Argoty; Marzieh Haghighi; Gerald J. Sun; Elizabeth Y. Choe; Aleksandra Markovets; J. Carl Barrett; Zhongwu Lai; Etai Jacob (npj Precision Oncology)
Abstract Circulating tumor DNA is a critical biomarker in cancer diagnostics, but its accurate interpretation requires careful consideration of clonal hematopoiesis (CH), which can contribute to variants in cell-free DNA and potentially obscure true tumor-derived signals. Accurate detection of somatic variants of CH origin in plasma samples remains challenging in the absence of matched white blood cells sequencing. Here we present an open-source machine learning framework (MetaCH) which classifies variants in cfDNA from plasma-only samples as CH or tumor origin, surpassing state-of-the-art classification rates.